2016
DOI: 10.1128/aac.01861-15
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Polyphosphate against Prevotella intermedia in Planktonic Phase and Biofilm

Abstract: c Polyphosphate (polyP) has gained a wide interest in the food industry due to its potential as a decontaminating agent. In this study, we examined the effect of sodium tripolyphosphate (polyP3; Na 5 P 3 O 10 ) against planktonic and biofilm cells of Prevotella intermedia, a major oral pathogen. The MIC of polyP3 against P. intermedia ATCC 49046 determined by agar dilution method was 0.075%, while 0.05% polyP3 was bactericidal against P. intermedia in time-kill analysis performed using liquid medium. A crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 60 publications
1
15
0
1
Order By: Relevance
“…For the reason that biofilm can act as a reservoir of antibiotic resistance, it is of clinical significance to develop alternative antimicrobial approaches for controlling antibioticresistant P. intermedia. 7 In the present study, study group showed reduction in colony count of P. intermedia after being exposed to GaAlAs diode laser for 1 minute from 369 to 229, 134 and 41 after serial dilution of in ThioGlycollate Broth in 1:10, 1:50 and 1:100 ratios which was statistically significant with p value <0.0001.…”
Section: Discussionsupporting
confidence: 52%
“…For the reason that biofilm can act as a reservoir of antibiotic resistance, it is of clinical significance to develop alternative antimicrobial approaches for controlling antibioticresistant P. intermedia. 7 In the present study, study group showed reduction in colony count of P. intermedia after being exposed to GaAlAs diode laser for 1 minute from 369 to 229, 134 and 41 after serial dilution of in ThioGlycollate Broth in 1:10, 1:50 and 1:100 ratios which was statistically significant with p value <0.0001.…”
Section: Discussionsupporting
confidence: 52%
“…That is, polyP3 exerted bactericidal activity (defined as a ≥ 99.9% killing rate within 24 h [25]) against planktonic cells of all three Porphyromonas species at lower concentrations than the MICs determined by the agar dilution method. Similarly, the MIC of polyP against the human periodontopathic P. gingivalis and P. intermedia was 600–750 mg/L by the agar dilution method, whereas polyP in the liquid medium showed a bactericidal effect against the two bacteria at sub-MIC levels [2223]. Some antimicrobials, including polyP, may exert a higher effect in liquid media than in solid media, presumably because the liquid medium provides an environment favorable for the migration and diffusion of the antimicrobial agents, allowing easy contact with individual bacterial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial culture suspension, adjusted to an optical density of 0.1 at 600 nm (OD 600 = 0.1) in B-HK, was dispensed into a polystyrene 96-well plate (100 μL/well) containing B-HK (100 μL/well) with or without polyP3. As dead bacterial cells could attach to the surface of the polystyrene culture plates [2326], heat-killed (100°C for 10 min) bacterial cells were included as controls. After 24 h of incubation, planktonic and loosely bound bacterial cells were removed by aspiration of the spent media.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each bacterial strain grown to exponential phase was adjusted to an optical density at 600 nm (OD 600 ) of 0.1 with new broth. Each Ti specimen was placed in each well of 24-well polystyrene plate containing the adjusted bacterial suspension, then the plate was incubated at 37°C aerobically, as described previously [21,22]. After 24 h, the specimens were removed and the bacterial biofilm formed on Ti surface was washed with physiological saline, then fixed with 2.5% glutaraldehyde in 0.1 M phosphate buffer for 1 h at room temperature and rinsed three times for 10 min each with distilled water.…”
Section: Bacterial Biofilm Formationmentioning
confidence: 99%